Aktivitas Antijamur Ekstrak Etanol Kulit Buah Ananas comosus (L) Merr. terhadap Trichophyton mentagrophytes dan Malassezia furfur - Octaviani, Melzi; Fikrani, Delvian; Susanti, Emma (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2020)
The fruit rinds of pineapple is part of pineapple fruit (Ananas comosus (L) Merr.) which is usually not used. The phytochemical screening results from extract ethanol of skin pineapple, included flavonoids, alkaloids phenolics, steroids and saponins that can inhibit the growth of microorganisms. The purpose of this research is to know the antifungal activity of ethanol extract pineapple skin against Trichophyton mentagrophytes and Malassezia furfur. The study was performed using disc diffusion method with the varyation concentrations of ethanol extract from the pineapple skin of 25%, 12.5%, 6.25%, 3.125% and 1.5625% w/v, respectively and the positive control is nystatin and negative control is DMSO. The diameter of the inhibition zone formed on the ethanol extract test of the skin pineapple against Trichophyton mentagrophytes and Malassezia furfur at a concentration of 25% was 22.73 mm and 24.90 mm, respectively. This indicated that the extract etanol of skin pineapple has antifungal activity